Free latissimus dorsi flap for upper extremity reconstruction in a 9-month-old. Issue 1 (1st January 2021) - Wagner, Ryan D.; Yang, Jacqueline S.; Bryant, Brittany E.; Pederson, William C.; Izaddoost, Shayan A.
Abstract: Successful outcomes for free tissue transfer are well-documented in pediatric patients but less so in infants. Challenges with infants are unique and include implications of prolonged anesthetic exposure. We present a 9-month-old female who underwent a free latissimus dorsi flap to reconstruct a congenital upper extremity lesion threatening limb development.